1944
DOI: 10.1104/pp.19.2.338
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Quantities in Growing Cotton Bolls

Abstract: WITH TWO FIGURES)Regional variety tests have shown that the tensile strength of cotton fibers of any giveni variety is influenced by environmental conditions. In general, the fiber seems to have greater strenigth wheni plant growth is checked by deficient water and less strengicth when water is not a limitinog factor. This observation has led to the assumption that the strength of cotton fibers might be influenced appreciably by the turgor of the developing fiber cells. If this assumption were correct, a knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1945
1945
1982
1982

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Kerr & Anderson (49) observed that while the osmotic pressure of sap expressed from young cotton seeds exceeded their DPD as measured gravi metrically, in seeds 24 days old the DPD exceeded the osmotic pressure, the difference increasing with age of the seeds. Neither the DPD nor the amount of water absorbed was decreased by potassium cyanide or other treatments which inhibit respiration, and it was concluded that the vacuolar sap prob ably was contaminated with sap from the cytoplasm, released by freezing prior to expression of sap.…”
Section: Evidences Of Active or N Onosmotic Absorptionmentioning
confidence: 98%
“…Kerr & Anderson (49) observed that while the osmotic pressure of sap expressed from young cotton seeds exceeded their DPD as measured gravi metrically, in seeds 24 days old the DPD exceeded the osmotic pressure, the difference increasing with age of the seeds. Neither the DPD nor the amount of water absorbed was decreased by potassium cyanide or other treatments which inhibit respiration, and it was concluded that the vacuolar sap prob ably was contaminated with sap from the cytoplasm, released by freezing prior to expression of sap.…”
Section: Evidences Of Active or N Onosmotic Absorptionmentioning
confidence: 98%
“…Small samples from a single tissue type are more significant than large mixed samples. With any sample, dilution of the vacuolar sap by water liberated by alteration in physical organization of colloidal matter may constitute a real limitation (Newton, Brown, and Martin, 1926; Meyer, 1928; Jaccard and Frey- Wyssling, 1934 ; Roberts and Styles, 1939 ; Kerr and Anderson, 1944 ; Currier, 1944a). Walter and Weismann (1935) consider this not to be a source of error.…”
Section: Vol Of Turgorless Cellmentioning
confidence: 99%
“…In their opinion, the simplified method, used for DPD, yielded values which were too high, especially when leaves in a wilted or nearly wilted condition were measured. Kerr and Anderson (1944) That a considerable proportion of the DPD may at times be due to the development of high tensions has been emphasized by some. Such negative wall pressures, in intact leaves of trees, especially during periods of abnormally high water loss, may exceed the influence of osmotic effects on the DPD (seeCuv, 1936).…”
Section: Vol Of Turgorless Cellmentioning
confidence: 99%
See 2 more Smart Citations